The Phenomenology of Hair Pulling Urges in Trichotillomania: A Comparative Approach - Madjar, Shai; Sripada, Chandra S. (Frontiers in Psychology, 2016)
Trichotillomania is a disorder characterized by recurrent urges to pull out one’s hair, but the experiential characteristics of hair pulling urges are poorly understood. This study used a comparative approach to understand the subjective phenomenology of hair pulling: participants with trichotillomania symptoms were asked about their hair pulling urges as well as their urges to eat unhealthy foods. Participants who reported experiencing problematic unhealthy food urges were identified and asked to compare the phenomenological characteristics of their hair pulling and unhealthy food urges across a variety of dimensions. Results revealed significant differences for only some urge properties measured, and differences that existed were small to moderate in magnitude. Qualitative comparisons of the two urges revealed situational characteristics of hair pulling that could explain these small to moderate differences between the two urges. We conclude that hair pulling urges may be more comparable to ordinary urges such as unhealthy food urges than one might expect, but that hair pulling urges may nevertheless be rated as slightly more severe due to situational characteristics of these urges. This conception may improve clinician and lay understanding of the condition, assist with destigmatization efforts, and facilitate the development of treatment strategies.